The impact the of the imported inflation on the red meat costs of production in the wilaya of Biskra - Ababsa, Mostefa; Louhbaibat, Ahmed; Aoussi, Hani Amir (Dirassat Journal Economic Issue, 2021)
The aim of this study is to analyze the effect of the imported inflation on production cost of red meat in the Wilaya of Biskra, during the period 2000-2014, using the unit value index affecting the cost’s function of production of the red meat for the long term, using Cobb-Douglas function of production. Therefore, we have arrived to a negative effect of the imported inflation on the fodder production’s function, which can extend its effect on the cost’s function of production of red meat, which emphasizes the need to take measures to alleviate the imported inflation’s pressure on production of fodder and the red meat.